Diagnostic value of “t sign” on MRCP-MIP imaging in the evaluation of pancreas divisum (Annals of Medical Research, 2021)
Aim: To determine the “t sign” diagnostic criteria on MRCP-MIP imaging in patients with pancreas divisum (PD).Material and Methods: Between May 2013 and August 2019 a total of 1289 patients who underwent both ERCP and MRCP, were enrolled to the study. To select the patients with PD diagnosis on both MRCP and ERCP were planned. Patients were compared with control group. MRCP assessment included presence and type of PD, relationship of common bile duct on axial and coronal MIP-MRCP images. Test characteristics were introduced for demonstrating diagnostic value of “t sign” on MRCP in patients with PD in the study group compared with those in the control group. Analysis was performed using the Breeze/STAT statistical calculation with computation of the 95% confidence intervals (CIs). Results: Twenty-eight patients with diagnosis of PD according to the MRCP reports were selected for the study. Of the 28 cases, five patients without PD biliary morphology excluded from the study group due to ERCP results and one patient with the diagnosis of ”probable PD” by the ERCP report was also excluded. Twenty-two patients had typical PD (95.45 %) and incomplete PD was demonstrated in one case (4.55%) . Sensitivity, specificity, positive predictive value, negative predictive value and accuracy value of MRCP-MIP imaging for demonstrating PD with using “t sign” criteria were 100%, 99%, 100%, 99% and 99% respectively. (95% CI).. Conclusion: We concluded that, dorsal main pancreatic duct (MPD) and common bile duct cross relation was identified in all complete PD patients as a “t sign” diagnostic criteria on coronal MIP-MRCP images.
Keywords: Pancreas; magnetic resonance cholangiopancreatography; pancreatitis; pancreatic duct.